Hipólito Unánue, Primer Ministro de Econompia del Perú (1821-1823) - Seiner, Lizardo A. (2020)
The role of Hipolito Unanue in shaping the new Republic of  Peru was important. He headed the Ministry of Finance for two non-consecutive periods. In the first one he dispatched almost two years, between August 1821 and June 1823, while in the second one, he worked between September 1823 and February 1824. In September 1822 he presented a report to the Constituent Congress. In it, he gives an account of the various dispositions that he dictated in order to face the income deficit that the so-called fiscal box was facing. His conservative initiatives to achieve a fiscal balance are recognized today.